2017
DOI: 10.1111/jace.14887
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer lead‐free piezoceramic composites: Influence of co‐firing on microstructure and electromechanical behavior

Abstract: In this study lead-free 2-2 and 0-3 ceramic/ceramic composites comprised of the non-ergodic relaxor 0.93(Bi 1/2 Na 1/2 )TiO 3 -0.07BaTiO 3 and ergodic relaxor 0.94Bi 0.5 (Na 0.75 K 0.25 ) 0.5 TiO 3 -0.06BiAlO 3 were investigated. The macroscopic electromechanical behavior was characterized as a function of continuent content, revealing an enhancement in the unipolar strain from the multilayer composite structure. Systematic evaluation of the effects of co-sintering on microstructural properties, such as grain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…For instance, as pores have a relative permittivity of 1, charge accumulation during the application of an electric field can occur at the interface between the pore and the FE, resulting in a localized large electric field. As a result, the bilayer composition of NBT-7BT with 20 vol% 0.94Bi 0.5 (Na 0.75 K 0.25 )0.5TiO 3 -0.06BiAlO 3 showed the highest increase in pore size and therefore also the highest strain response as shown by Ayrikyan et al [32].…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…For instance, as pores have a relative permittivity of 1, charge accumulation during the application of an electric field can occur at the interface between the pore and the FE, resulting in a localized large electric field. As a result, the bilayer composition of NBT-7BT with 20 vol% 0.94Bi 0.5 (Na 0.75 K 0.25 )0.5TiO 3 -0.06BiAlO 3 showed the highest increase in pore size and therefore also the highest strain response as shown by Ayrikyan et al [32].…”
Section: Introductionmentioning
confidence: 69%
“…Even though composites have demonstrated promising results, the underlying mechanisms are still not fully understood, such as the internal residual stresses and porosity arising from different sintering trajectories of the end members, interdiffusion between the constituents, and the influence of strain coupling. For this reason, studies on 2-2 composites have been conducted on different material systems to highlight certain aspects [32][33][34][35]. In particular, the work by Zhang et al [35] showed the importance of strain-coupling in multilayer composites of 0.91(Na 1/2 Bi 1/2 )TiO 3 -0.06BaTiO 3 -0.03AgNbO 3 and NBT-7BT by varying the orientation of the interfaces parallel and perpendicular to the applied electric field, where it was possible to remove the influence of the polarization coupling (PC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that further differentiate the contribution of lateral strain coupling from the polarization coupling would be helpful. More recent work has also found that internal stresses due to different sintering shrinkages and thermal expansions between constituents can result in changes in microstructure and porosity, which are also expected to affect the electromechanical properties. The interface between the constituents can weaken both the mechanical and polarization coupling.…”
Section: Introductionmentioning
confidence: 99%
“…[16] To decouple these effects in 0-3 composites is challenging, making the determination of their relative contributions nontrivial. More recent work has also found that internal stresses due to different sintering shrinkages and thermal expansions between constituents can result in changes in microstructure and porosity, [18] which are also expected to affect the electromechanical properties. In the parallel case, the strain in the poling direction is coupled through the interface, while in the perpendicular case, the polarization charge is coupled.…”
mentioning
confidence: 99%